2020
DOI: 10.1002/adhm.202000305
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Therapeutic Reservoir Systems for Diverse Clinical Applications in Large Animal Models

Abstract: In article number 2000305 by Ellen T. Roche, Eimear B. Dolan, and co‐workers, a new regenerative reservoir platform (Regenervoir) is described for use in large animal models that are easily translated to human studies, with relevance to cardiac, abdominal, and soft tissue pathologies. Regenervoir incorporates multiple novel design features essential for clinical translation, with a focus on scalability, mechanism of delivery, fixation, and filling/refilling with a therapeutic cargo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…This novel macroencapsulation device not only improved tissue integration and peri-implant vascularity but also has shown to be retrievable and refillable, which is an important consideration for regulatory purposes [17]. We have previously demonstrated the ability to scale these devices for large animal models, while still allowing low profile, minimally invasive delivery, aligned to common interventional procedures [17,64].…”
Section: Discussionmentioning
confidence: 99%
“…This novel macroencapsulation device not only improved tissue integration and peri-implant vascularity but also has shown to be retrievable and refillable, which is an important consideration for regulatory purposes [17]. We have previously demonstrated the ability to scale these devices for large animal models, while still allowing low profile, minimally invasive delivery, aligned to common interventional procedures [17,64].…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference between the left and right sides for polygons adds complexity when planning the procedure. We have, recently, described a porous refillable reservoir and a minimally invasive procedure to deliver it between muscle layers in a pig study, with securement to the fascia via a minimally invasive scope and trocar system [ 51 ]. We have shown that a space can be created, and a reservoir (similar size as discussed here) deployed in an atraumatic manner and secured with current minimally invasive fixation tools.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that a space can be created, and a reservoir (similar size as discussed here) deployed in an atraumatic manner and secured with current minimally invasive fixation tools. These refillable reservoirs are manufactured from soft materials such as thermoplastic polyurethane, with an elastic modulus approximately 15 MPa [ 52 ], similar to the tissue extracellular matrix [ 53 ], which enables minimally invasively delivery through a trocar [ 51 ] and also allows conformation of the device during bending and twisting within the tissue plane. This favourable interaction with the surrounding environment will be essential for long-term device performance but also patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, multiple islet infusions are often required to reverse insulin dependence. [ 186 ] Many of the commercially available [ 5,80 ] and research stage devices [ 86,176,187 ] have incorporated features (tubing and self‐sealing subcutaneous or transcutaneous ports) to enable the repeated delivery of cell cargo. This design consideration is particularly relevant to allow dosing and cargo adjustment if one thinks about future incorporation of continuous sensing of implant function.…”
Section: Minimizing Foreign Body Responsementioning
confidence: 99%